2015
DOI: 10.9738/intsurg-d-14-00160.1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Nonoperative Management of Blunt Splenic Injury—Asian Experience

Abstract: Management of blunt splenic injury (BSI) has evolved with a focus on nonoperative management (NOM) and spleen preservation. Factors predictive of failure of NOM are yet ill defined. We report our experience of outcomes of NOM of BSI and evaluate factors that predict failure. This is a retrospective study from a prospective trauma registry of a university-affiliated major trauma center over a 4 ½-year period. All the patients admitted with BSI from January 2004 to May 2009 were included in this study. Demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(23 reference statements)
0
3
0
1
Order By: Relevance
“…Thus, spleen preservation was not deemed ideal. Furthermore, the risk of opportunistic post-splenectomy infections remains low, especially in non-paediatric patient profile 15 16. Recently, Zheng et al reported laparoscopic spleen-preserving distal pancreatic resection in a 51-year-old man diagnosed with ECIPAS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, spleen preservation was not deemed ideal. Furthermore, the risk of opportunistic post-splenectomy infections remains low, especially in non-paediatric patient profile 15 16. Recently, Zheng et al reported laparoscopic spleen-preserving distal pancreatic resection in a 51-year-old man diagnosed with ECIPAS.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with spontaneous splenic rupture with hemoperitoneum in a background of metastatic disease, splenectomy is undisputed. 7 In a stable patient, if expertise is available, minimal access surgery can potentially improve short term outcomes. 8 As we had expertise available 9 10 for laparoscopic elective and acute care surgery, we performed a laparoscopic splenectomy successfully in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic distal pancreatectomy remains the gold standard; however, in our patient we anticipated a difficult operative course due to multiple episodes of acute pancreatitis and previous gastric perforation, hence the decision for open surgery. We also performed splenectomy as (a) it reduces blood loss due to control of splenic vessels and (b) adult immunocompetent patients rarely manifest with opportunistic postsplenectomy sepsis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%